Ideology at work: reconsidering ideology, the labour process and workplace resistance. Issue 5 (13th June 2017) - Lloyd, Anthony
Abstract : Purpose: The purpose of this paper is to consider existing debates within the sociology of work, particularly the re-emergence of labour process theory (LPT) and the "collective worker", in relation to resistance at work. Through presentation of primary data and a dialectical discussion about the nature of ideology, the paper offers alternative interpretations on long-standing debates and raises questions about the efficacy of workplace resistance. Design/methodology/approach: The design of this methodology is an ethnographic study of a call centre in the North-East of England, a covert participant observation at "Call Direct" supplemented by semi-structured interviews with call centre employees. Findings: The findings in this paper suggest that resistance in the call centre mirrors forms of resistance outlined elsewhere in both the call centre literature and classical workplace studies from the industrial era. However, in presenting an alternative interpretation of ideology, as working at the level of action rather than thought, the paper reinterprets the data and characterises workplace resistance as lacking the political potential for change often emphasised in LPT and other workplace studies. Originality/value: The original contribution of this paper is in applying an alternative interpretation of ideology to a long-standing debate. In asking sociology of work scholars to consider the "reversal of ideology", it presents an alternative perspective on resistance in the workplace and raises questions about the efficacy of workplace disobedience.